2020
DOI: 10.1096/fj.201902467r
|View full text |Cite
|
Sign up to set email alerts
|

Circulating neutrophil subsets in advanced lung cancer patients exhibit unique immune signature and relate to prognosis

Abstract: The accumulation of circulating low‐density neutrophils (LDN) has been described in cancer patients and associated with tumor‐supportive properties, as opposed to the high‐density neutrophils (HDN). Here we aimed to evaluate the clinical significance of circulating LDN in lung cancer patients, and further assessed its diagnostic vs prognostic value. Using mass cytometry (CyTOF), we identified major subpopulations within the circulating LDN/HDN subsets and determined phenotypic modulations of these subsets alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 58 publications
(139 reference statements)
4
97
0
Order By: Relevance
“…VDJViewer was specifically developed with the intention to provide single cell data processing for users that do not have advanced bioinformatic expertise, therefore making immunologic single cell data more accessible (69). In addition to modeling antigen markers, scRNA seq, and meta data, this application can also perform pseudo-time analysis and dimensionality reduction (69). As more data and platforms like VDJViewer become available, there is also a need to improve the models that operate within a given platform.…”
Section: Pre-print Platformsmentioning
confidence: 99%
“…VDJViewer was specifically developed with the intention to provide single cell data processing for users that do not have advanced bioinformatic expertise, therefore making immunologic single cell data more accessible (69). In addition to modeling antigen markers, scRNA seq, and meta data, this application can also perform pseudo-time analysis and dimensionality reduction (69). As more data and platforms like VDJViewer become available, there is also a need to improve the models that operate within a given platform.…”
Section: Pre-print Platformsmentioning
confidence: 99%
“…Interestingly, LDNs have been identified in patients with breast cancer, lung cancer, head and neck cancers, urologic cancers, and lymphoma ( 7 , 99 101 ). In patients with advanced lung cancer, it was reported that higher proportion of LDNs (>10%) predicted poorer survival ( 102 ). These observations are in keeping with the pro-tumorigenic and pro-metastatic functions associated with LDN/N2 neutrophils.…”
Section: Clinical Importance: Future Perspectives On Treatmentmentioning
confidence: 99%
“…Neutrophils can secrete essential factors, including IL-8, VEGF, and elastase for tumor growth and metastases. 21 Shaul et al 29 suggested that the peripheral blood in patients with advanced lung cancer was the preferred site for accumulation of low-density neutrophils that are associated with poor prognosis. Moreover, proinflammatory neutrophils can release neutrophil extracellular traps (NETs) to capture pathogens and function as an antibacterial barrier in the body, although these neutrophils are also associated with the incidence of chronic inflammation and cancer.…”
Section: Dovepressmentioning
confidence: 99%